Biotic habitats as refugia under ocean acidification. Issue 1 (16th September 2021) - Falkenberg, Laura J; Scanes, Elliot; Ducker, James; Ross, Pauline M
Abstract : Habitat-forming organisms, such as macroalgae and seagrasses, could ameliorate the effects of ocean acidification by countering the alterations to water chemistry through photosynthesis. Importantly, whether they will create refugia will be context dependent and influenced by local traits, meaning management at the local scale could fundamentally shape global change impacts. Abstract: Habitat-forming organisms have an important role in ameliorating stressful conditions and may be of particular relevance under a changing climate. Increasing CO2 emissions are driving a range of environmental changes, and one of the key concerns is the rapid acceleration of ocean acidification and associated reduction in pH. Such changes in seawater chemistry are anticipated to have direct negative effects on calcifying organisms, which could, in turn, have negative ecological, economic and human health impacts. However, these calcifying organisms do not exist in isolation, but rather are part of complex ecosystems. Here, we use a qualitative narrative synthesis framework to explore (i) how habitat-forming organisms can act to restrict environmental stress, both now and in the future; (ii) the ways their capacity to do so is modified by local context; and (iii) their potential to buffer the effects of future change through physiological processes and how this can be influenced by management adopted. Specifically, we highlight examples that consider the ability of macroalgae and seagrasses to alter water carbonate chemistry, influence resident organisms under current conditions and their capacity to do so under future conditions, while also recognizing the potential role of other habitats such as adjacent mangroves and saltmarshes. Importantly, we note that the outcome of interactions between these functional groups will be context dependent, influenced by the local abiotic and biotic characteristics. This dependence provides local managers with opportunities to create conditions that enhance the likelihood of successful amelioration. Where individuals and populations are managed effectively, habitat formers could provide local refugia for resident organisms of ecological and economic importance under an acidifying ocean.